A Comprehensive Safety Evaluation of 68Ga-Labeled Ligand Prostate-Specific Membrane Antigen 11 PET/CT in Prostate Cancer: The Results of 2 Prospective, Multicenter Trials. (July 2017) - Nielsen, Julie B.; Zacho, Helle D.; Haberkorn, Uwe; Nielsen, Karin M.; Dettmann, Katja; Langkilde, Niels C.; Petersen, Lars J.
Abstract : Purpose: The aim of this study was to evaluate the clinical safety profile of the 68 Ga-PSMA-11 ligand for PET/CT imaging in prospective clinical trials. Methods: Eighty-eight patients with newly diagnosed or recurrent prostate cancer participated in 2 prospective trials. Safety reporting was identical in the 2 trials. The 68 Ga-PSMA-11 ligand was administered as 2 MBq/kg body weight (mean, 9.2 μg, 9.7 nmol). The reporting of clinical adverse events (AEs) and the measurement of blood pressure (BP) and heart rate (HR) were performed prior to injection (baseline); immediately after injection of 68 Ga-PSMA-11 (postinjection); at 1, 10, and 60 minutes after injection; and after acquisition of the PET/CT scan (postscan). All hemodynamic assessments were performed in the supine position, except for the postscan measurement (sitting). The patients were interviewed regarding any AEs at baseline, postinjection, or postscan. In addition, the patients were instructed to report any AEs during the investigation and to contact the investigator if AEs occurred during the rest of the day. Adverse events were classified as mild, moderate, or severe by the patients and categorized by the investigator using the CTCAE (Common Terminology Criteria for Adverse Events) version 4.0. Results: There were no reported clinical AEs. There were significant decreases in systolic BP ( P < 0.001) and HR ( P < 0.001) over time. In comparison, the diastolic BP increased significantly ( P < 0.001). After removal of the last observation (supine position), there was no time-dependent change in systolic or diastolic BP, but the significant change in HR remained. The mean changes over the entire observation period were minimal (systolic BP, −6 to 5 mm Hg; diastolic BP, −2 to 3 mm Hg; HR, decrease of 5 beats/min). No patients developed hypotension. Fifty-five patients presented with hypertension at baseline, which increased by 1 CTCAE grade in 15 patients and by 2 grades in 2 patients. A large number of cases of asymptomatic (grade 1) bradycardia were observed, primarily in patients with preexisting bradycardia. One patient developed transient grade 1 tachycardia. No patients required medical intervention for cardiovascular perturbations. Conclusions: 68 Ga-PSMA-11 PET/CT was very well tolerated. We consider 68 Ga-PSMA-11 to be safe for human application.